KINERJA DITINJAU DARI GAYA KEPEMIMPINAN, PROFESIONALISME, ETIKA DAN BEBAN KERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SUKOHARJO - Lucia Purnanita Kristianingsih; Istiatin; Bambang Mursito (JURNAL ILMIAH EDUNOMIKA, 2025)
The aim of this study is to determine the simultaneous and partial effects of the variables of leadership style, level of professionalism, ethics, and workload on the performance of employees at the Department of Education and Culture of Sukoharjo Regency. This research was conducted at the Department of Education and Culture of Sukoharjo Regency. It is a correlational study, which seeks to explain asymmetric relationships among the variables studied. The research sample consisted of 98 employees of the Department of Education of Sukoharjo Regency. Data were collected through questionnaires, interviews, observations, and documentation. The data analysis techniques used include multiple regression analysis, F-test, t-test, and the coefficient of determination (R²). The results of the study show that leadership style, level of professionalism, ethics, and workload have a positive and significant effect on the performance of employees at the Department of Education and Culture of Sukoharjo Regency, both partially and simultaneously. The higher the leadership style quality, professionalism, ethics, and workload, the better the performance of the employees at the Sukoharjo Regency Education Department. Keywords: Leadership Style, Professionalism, Ethics, Workload, Performance